POTENSI DAN KENDALA PROGRAM PERCEPATAN PENURUNAN STUNTING DI PROVINSI BALI - Nursanyoto, Hertog; Adhi, Kadek Tresna; Kusumajaya, Anak Agung Ngurah; Mubasyiroh, Rofingatul; Sudikno, Sudikno; Nainggolan, Olwin; Sutiari, Ni Ketut; Suarjana, I Made; Januraga, Pande Putu (Persagi, 2023)
Bali has the potential for good health resources. That is why Bali has been identified as the province with the lowest prevalence of stunting. However, this success should not make stakeholders think this problem is resolved. Bali still has problems which, if not addressed, will trigger a further increase in the prevalence of stunting. Considering this, it is deemed necessary to explore the perspectives of nutrition fieldworkers and other stakeholders regarding the problem of stunting in Bali. This research aims to explore the potential and constraints to accelerating stunting reduction in Bali. This is qualitative research conducted between June and July 2022. Data was collected through in-depth interviews and focus group discussions. This study found that access to affordable health services is the main potential to support the acceleration of stunting reduction. Apart from that, there is a Balinese Traditional Village Council which always synergizes with government programs for the welfare of the community. The low quality of cadres is an obstacle to the success of the program. Many parents hesitate to take their children to posyandu because they are not satisfied with the cadre's services. Apart from that, there are other inhibiting factors, such as society's wrong understanding of stunting, teenage marriage, lack of environmental hygiene and sanitation, and inappropriate parenting patterns. This condition needs attention so that the acceleration of stunting reduction in Bali can be achieved as optimally as possible.